Community-based Interventions – International Development, Government and Community - Arora, Nikita (The Meducator, 2013)
Non-governmental organizations (NGOs) are often criticized for their work in the healthcare sectors of developing countries. Recently, they have been moving from a projectized to sectoral support approach in an attempt to respond to this critique. Community-based intervention is a sectoral technique that can be used to exploit the community as a resource to provide the community itself with support in ways that the limited human resources in the healthcare sectors of developing countries currently cannot. The peer group intervention and community health worker are both tested strategies that have resulted in positive outcomes in the healthcare sectors of disadvantaged areas. Although community support systems may be limited in technical skill, a new body of research indicates that this intervention can nonetheless be a predictor of improved management of chronic illnesses that present high disease burden. By working with local stakeholders, NGOs may be able to effectively facilitate this intervention to promote sustainable positive health outcomes. By evaluating the effectiveness of the community-based intervention in Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) management in Malawi, a greater understanding of its role can be gained in a more tangible manner.